Ennius. Annales. Book I (translation, commentary) - Alexander Podossinov; Alexander Mankov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
Quintus Ennius (239‒169 BC) was a Latin poet who introduced hexameter to Latin poetry. His main work, Annales, an epic poem consisting of 18 books, is devoted to the history of Rome. Its text is preserved in fragments, the size of the greater part of which does not exceed one line. The total number of lines is 676 (in O. Skutsch’s edition). This publication is a result of the work of a seminar on translating Latin writers under guidance of Prof. A. Podossinov. In this seminar the entire preserved text of the Annals has been translated into Russian in hexameter for the fi rst time. Some fragments were earlier translated by S. Osherov for the “Anthology of Early Roman Literature”; these translations are included in our publication. Translations made by participants of the seminar are marked with *. The translation is based on E.H. Warmington’s edition; the Latin text is given according to this edition as well. In preparing the commentary we also used the edition by O. Skutsch. The authors of translation and commentaries are A. Denisov, E. Denshchikova, S. Fedotov, A. Ivlev, A. Mankov, Yu. Pekov, A. Podossinov, O. Ryabenko, I. Smirnova, S. Tereshkov, A. Voskresensky. We are grateful to E. Ilyushechkina for her help in preparing this publication.